Sub-regional disparities in the use of antenatal care service in Mauritania: findings from nationally representative demographic and health surveys (2011–2015) - Shibre, Gebretsadik; Zegeye, Betregiorgis; Ahinkorah, Bright O.; Idriss-Wheeler, Dina; Keetile, Mpho; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Skilled antenatal care (ANC) has been identified as a proven intervention to reducing maternal deaths. Despite improvements in maternal health outcomes globally, some countries are signaling increased disparities in ANC services among disadvantaged sub-groups. Mauritania is one of sub-Saharan countries in Africa with a high maternal mortality ratio. Little is known about the inequalities in the country’s antenatal care services. This study examined both the magnitude and change from 2011 to 2015 in socioeconomic and geographic-related disparities in the utilization of at least four antenatal care visits in Mauritania. Methods Using the World Health Organization’s Health Equity Assessment Toolkit (HEAT) software, data from the 2011 and 2015 Mauritania Multiple Indicator Cluster Surveys (MICS) were analyzed. The inequality analysis consisted of disaggregated rates of antenatal care utilization using four equity stratifiers (economic status, education, residence, and region) and four summary measures (Difference, Population attributable risk, Ratio and Population attributable fraction). A 95% Uncertainty Interval was constructed around point estimates to measure statistical significance. Results Substantial absolute and relative socioeconomic and geographic related disparities in attending four or more ANC visits (ANC4+ utilization) were observed favoring women who were richest/rich (PAR = 19.5, 95% UI; 16.53, 22.43), educated (PAF = 7.3 95% UI; 3.34, 11.26), urban residents (D = 19, 95% UI; 14.50, 23.51) and those living in regions such as Nouakchott (R = 2.1, 95% UI; 1.59, 2.56). While education-related disparities decreased, wealth-driven and regional disparities remained constant over the 4 years of the study period. Urban-rural inequalities were constant except with the PAR measure, which showed an increasing pattern. Conclusion A disproportionately lower ANC4+ utilization was observed among women who were poor, uneducated, living in rural areas and regions such as Guidimagha. As a result, policymakers need to design interventions that will enable disadvantaged subpopulations to benefit from ANC4+ utilization to meet the Sustainable Development Goal (SDG) of reducing the maternal mortality ratio (MMR) to 140/100, 000 live births by 2030.